Carbohydrate-derived aminoalcohol ligands for asymmetric Reformatsky reactions - Emmerson, D; Hems, W; Davis, B (2005)
Members of a family of functionally and stereochemically diverse d-glucosamine-derived tertiary aminoalcohol ligands have been used to promote the asymmetric Reformatsky reaction. The β-hydroxyester product tert-butyl 3-phenyl-3-hydroxy-propanoate was obtained enriched in either the (+)-(R) (up to 74% ee) or (-)-(S) (up to 42% ee) enantiomer depending on the choice of ligand. Although the selectivities are modest in absolute terms they represent some the better selectivities obtained to date for this reaction. A 1H NMR study was conducted to investigate this selectivity and suggested a secondary binding mode between ligand and zinc in addition to the expected N-2, O-3 coordination. © 2004 Elsevier Ltd. All rights reserved.